Studi Spesies Kepiting Bakau di Ekosistem Mangrove Batu Ampar, Kalimantan Barat - Tia Nuraya; Lalu Panji Imam Agamawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to identify mud crab species inhabiting the mangrove ecosystem of Batu Ampar, Kubu Raya Regency, West Kalimantan. Sampling was conducted from 26 October – 2 November 2024 during low tide using manual hand-catching, traditional traps (bubu), and fishermen’s catches obtained through interviews. A total of 20 crab individuals were collected and identified based on external morphological characteristics, referring to identification keys from WWF-Indonesia and the World Register of Marine Species (WoRMS). The results identified two dominant species, Scylla serrata and Scylla paramamosain. The main morphological differences included carapace coloration, claw size and shape, and the number and form of frontal spines. Among the total samples, S. serrata was more dominant compared to S. paramamosain. Interviews with fishers also revealed a body size classification commonly used in trade, namely Size A (≥ 600 g) and Size B (± 200 g), which directly influenced market prices. These findings confirm that the Batu Ampar mangrove ecosystem supports more than one economically valuable mud crab species. The study provides baseline information that can serve as an initial reference for sustainable management and conservation of mud crabs in coastal West Kalimantan